2010
DOI: 10.1007/s11248-010-9472-8
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency of BRCA1 knockout using rAAV-mediated gene targeting: developing a pig model for breast cancer

Abstract: Germline inactivating mutations of the breast cancer associated gene 1 (BRCA1) predispose to breast cancer and account for most cases of familiar breast and/or ovarian cancer. The pig is an excellent model for medical research as well as testing of new methods and drugs for disease prevention and treatment. We have generated cloned BRCA1 knockout (KO) Yucatan miniature piglets by targeting exon 11 using recombinant adeno-associated virus (rAAV)-mediated gene targeting and somatic cell nuclear transfer by Handm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 34 publications
1
63
0
3
Order By: Relevance
“…The overall pregnancy rate for HMC has increased from about 55 % to over 80 % according to the latest figure reported by two laboratories (in Denmark and China, respectively) that use HMC for large scale pig cloning (Schmidt et al 2010). However, further improvements are still required as high frequencies of prenatal and postnatal death of the cloned pigs are observed by us and others (Rogers et al 2008a;Luo et al 2011c;Wei et al 2012. Insufficient reprogramming of the somatic cell genome is suggested to be the major cause of these abnormalities, as aberrant DNA methylation was found in the cloned pigs with abnormal phenotypes (Kang et al 2001;Xue et al 2002). However, we also found that phenotypically normal cloned pigs are highly similar to non-cloned pigs in their genome-wide DNA methylation levels (Gao et al 2011a;Gao et al 2011b).…”
Section: (Weiss Et Al 2009)mentioning
confidence: 97%
See 2 more Smart Citations
“…The overall pregnancy rate for HMC has increased from about 55 % to over 80 % according to the latest figure reported by two laboratories (in Denmark and China, respectively) that use HMC for large scale pig cloning (Schmidt et al 2010). However, further improvements are still required as high frequencies of prenatal and postnatal death of the cloned pigs are observed by us and others (Rogers et al 2008a;Luo et al 2011c;Wei et al 2012. Insufficient reprogramming of the somatic cell genome is suggested to be the major cause of these abnormalities, as aberrant DNA methylation was found in the cloned pigs with abnormal phenotypes (Kang et al 2001;Xue et al 2002). However, we also found that phenotypically normal cloned pigs are highly similar to non-cloned pigs in their genome-wide DNA methylation levels (Gao et al 2011a;Gao et al 2011b).…”
Section: (Weiss Et Al 2009)mentioning
confidence: 97%
“…However, HMC will also become an important cloning method for generating GM pigs. Although only a few GM pigs have reportedly been generated by HMC (Kragh et al 2009;Jakobsen et al 2011;Luo et al 2011c), we have since made additional GM pigs by HMC as still unpublished models for atherosclerosis, psoriasis, metabolic syndrome and cancer. The overall pregnancy rate for HMC has increased from about 55 % to over 80 % according to the latest figure reported by two laboratories (in Denmark and China, respectively) that use HMC for large scale pig cloning (Schmidt et al 2010).…”
Section: (Weiss Et Al 2009)mentioning
confidence: 99%
See 1 more Smart Citation
“…Combining all these aspects, we built up a system that over four years produced very satisfying results , and today we have a number of cloned piglets that are transgenic for different serious human diseases (e.g. Luo et al, 2011;Staunstrup et al, 2012;Al-Mashhadi et al, 2013;Jakobsen et al, 2014 -and more are coming). Over the next years, the medical doctors will reveal if these transgenic piglets can serve as useful animal models for the different diseases.…”
Section: Using the Basic Circles In A Wider Contextmentioning
confidence: 99%
“…Genetically engineered pigs are used vastly in several medical fields (6), including models for cystic fibrosis (5,7,8), diabetes models (9, 10), immunology (11)(12)(13)(14)(15), neurodegenerative diseases (2,(16)(17)(18), cancer (19)(20)(21), ophthalmology (22,23) and cardiovascular diseases (24).…”
Section: Introductionmentioning
confidence: 99%